The Lateralization of Speech-Brain Coupling Is Differentially Modulated by Intrinsic Auditory and Top-Down Mechanisms - Assaneo, M. F.; Rimmele, J. M.; Orpella, J.; Ripollés, P.; de Diego-Balaguer, R.; Poeppel, D. (Frontiers in Integrative Neuroscience, 2019)
The lateralization of neuronal processing underpinning hearing, speech, language, and music is widely studied, vigorously debated, and still not understood in a satisfactory manner. One set of hypotheses focuses on the temporal structure of perceptual experience and links auditory cortex asymmetries to underlying differences in neural populations with differential temporal sensitivity (e.g. ideas advanced by Zatorre et al. 20021; Poeppel 20032). The Asymmetric Sampling in Time theory (AST; Poeppel 20032), builds on cytoarchitectonic differences between auditory cortices and predicts that modulation frequencies within the range of, roughly, the syllable rate, are more accurately tracked by the right hemisphere. To date, this conjecture is reasonably well supported, since - while there is some heterogeneity in the reported findings - the predicted asymmetrical entrainment has been observed in various experimental protocols. Here, we show that under specific processing demands, the rightward dominance disappears. We propose an enriched and modified version of the asymmetric sampling hypothesis in the context of speech. Recent work (Rimmele et al. 20183) proposes two different mechanisms to underlie the auditory tracking of the speech envelope: one derived from the intrinsic oscillatory properties of auditory regions; the other induced by top-down signals coming from other non-auditory regions of the brain. We propose that under non-speech listening conditions, the intrinsic auditory mechanism dominates and thus, in line with AST, entrainment is rightward lateralized, as is widely observed. However, (i) depending on individual brain structural/functional differences, and/or (ii) in the context of specific speech listening conditions, the relative weight of the top-down mechanism can increase. In this scenario, the typically observed auditory sampling asymmetry (and its rightward dominance) diminishes or vanishes.